Cross-Border Community Engagement: University Social Action to Foster Global Awareness in Perlis, Malaysia - R. Sabrina; Muhammad Irfan Nasution; Muhammad Fitra Zambak; Sigit Hardiyanto; Nugraha Pratama; Rini Astuti; Rai Rake Setyawan; Yoshida Sary (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
Activity devoted to the public international. This aim is to strengthen global awareness through the implementation of Cross-Border Community Engagement: University Social Action to Foster Global Awareness in Perlis, Malaysia. held on August 23, 2025, in Peta Faizuddin Centre of Educational Excellence (FCoEE –MAIPs), Perlis, Malaysia, and Muhammadiyah University Malaysia, as a form of collaboration between Doctoral Study Programs Management, Postgraduate Program of Muhammadiyah University of North Sumatra (UMSU), and FCoEE – MAIPs. The program focuses on raising awareness of the importance of education for poor children, strengthening social concern, and fostering international collaboration to empower communities. The method used is a participatory approach with stages of preparation, implementation, observation, and evaluation. Form activity covering provisioning to children, poor about the importance of education, perseverance, and patience in the face of life challenges, implementation of Focus Group Discussion (FGD) with the manager of FCoEE –MAIPs regarding concerns about social empowerment, as well as a visit to the field to learn and practice empowerment in the community that has been implemented by the institution partners. Data obtained through observation, participation, documentation, discussion, and reflection were then analysed using a descriptive qualitative approach. Results of the activities show that participants gain an understanding of the importance of education in building the future, create space to share knowledge and experience through FGDs between college students and international partners, and broaden their outlook on practice empowerment in community-based settings through field visits. Activities also strengthen the connection and partnership between the college and the institution, in terms of social implementation, devotion to the public, and cross-country. Implications activity. This shows that cross-border community engagement can be one approach to strengthening the role of social colleges, broadening global awareness, and advancing sustainable international collaborations in education, research, and community service for the public.